An electrode of the second kind for benzoate determination in medicinal syrups - Peres, A. M.; de Moraes, M.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP]; Melios, C. B. (Academic Press Inc., 1998)
This paper describes the construction of an electrode of the second kind, Pt\Hg\Hg-2(Bzt)(2)\graphite, sensitive to benzoate ion (Bzt). The electrode provides a near-Nernstian response (-58.19 mV/decade at 25 degrees C) to benzoate ion in the concentration range 1.11 x 10(-1) to 5.00 x 10(-4) M at pH 7.0 and ionic strength 0.500-3.00M, adjusted with NaClO4. The electrode is easily constructed, shows a fast response time, is low in cost, has excellent response stability, and has a lifetime greater than 24 months. which is much longer than those earlier reported for other systems. A further salient feature of the electrode is that perchlorate does not interfere in its response, which may be advantageous in the analysis of perchloric acid-treated samples. It was applied to the determination of sodium benzoate in some commercial expectorating medicinal syrups using the standard additions method. The results obtained by the proposed procedure compare very favorably with those obtained through the reference method recommended by the United States Pharmacopeia. (C) 1998 Academic Press.